Adopting 4-H Club Bylaws - Keith G. Diem; Judy Levings; Ben Knowles (EDIS)
Why does a 4-H club (for youth ages 8–18) need bylaws? For the same reason our country needs a constitution! By having fair and written rules, the rights of all members can be protected. The following is a suggested format for 4-H bylaws. The bylaws below may be adapted to meet local conditions. Be sure to send a copy of your club’s approved bylaws to your county 4-H office. Include in the bylaws the date when they were approved and most recently revised. This 3-page fact sheet was written by Keith G. Diem, Judy Levings, and Ben Knowles, and published by the UF Department of 4-H Youth Development, July 2014.